Perlombaan Peringatan Maulid Nabi Muhammad SAW sebagai Upaya Menumbuhkan Nilai Religius Siswa di SMP Negeri 2 Sangatta Utara - Akmaliah, Qatrunnada Jinan; Muhabibudin, Nur (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
This Community Service Program (PKM) was conducted at SMP Negeri 2 Sangatta Utara to commemorate the birth of Prophet Muhammad SAW 1447 H. The main objectives were to strengthen religious values, foster social character, and enhance the spirit of tolerance within the school environment. The two-day event involved collaboration among university students, teachers, students, and the local community. The implementation used a descriptive qualitative approach with participatory observation techniques to describe the process and outcomes of the activities in the field. The results indicate a significant increase in student participation, with more than 85% of students (approximately 620 participants) actively engaging in religious competitions, public lectures, and charitable programs. The involvement of university students in event management contributed to high implementation effectiveness, reflected in 95% on-time activity completion and an observed increase in student discipline among 78% of participants. The charity program successfully distributed 120 donation packages to students in need. Furthermore, the presence of non-Muslim students, who simultaneously fulfilled their own religious activities, demonstrated strengthened tolerance practices, with 92% of teachers reporting a more inclusive school atmosphere during the event. Overall, this PKM initiative effectively strengthened the school’s religious culture, enhanced social solidarity, and fostered tolerant attitudes among students. Thus, collaboration between higher education institutions and schools proves to be an effective strategy for cultivating Islamic values and building inclusive and civilized character education.